2021
DOI: 10.3390/designs5040070
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Smart Home Technology Acceptance and Preference for Elderly in Dubai, UAE

Abstract: The elderly are the most predicted users for smart home technology in the United Arab Emirates and the population over 65 is expected to increase to 24.3% by 2030. Despite the rapid development of smart home technology, research has been mainly focused on technology development. To encourage conservative elderly users, however, smart home technology should be implemented for UAE elderly users to accept and integrate it into their daily lives. The objective of this paper is to analyze the preferences and needs … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(7 citation statements)
references
References 75 publications
(62 reference statements)
0
7
0
Order By: Relevance
“…As human become old, their physical functions deteriorate, and they suffer from various age-related chronic diseases and exhibit anxiety and depressive symptoms [5].…”
Section: Introductionmentioning
confidence: 99%
“…As human become old, their physical functions deteriorate, and they suffer from various age-related chronic diseases and exhibit anxiety and depressive symptoms [5].…”
Section: Introductionmentioning
confidence: 99%
“…Numerous studies have indicated the significance of the social relationships of older adults, including support and guidance from family and friends, in the adoption of technology ( 14 , 17 , 33 ). Due to the importance of family bonds in traditional Chinese culture, many citizens prefer the three-in-a-row model where parents and children provide intergenerational upward and downward support.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have examined the factors that influence the acceptance of smart home services by older adults, including personal and environmental perception factors. Personal perception factors comprise perceived ease of use, perceived usefulness, perceived cost ( 16 ), facilitating conditions ( 7 ),technology anxiety ( 17 ), and security and privacy concerns ( 16–18 ). Environmental perception factors include social influence ( 7 , 18 ), subjective norms ( 15 ), cultural influence ( 7 ), family management policies, and government policies ( 18 ).…”
Section: Related Workmentioning
confidence: 99%
See 1 more Smart Citation
“…It encompasses common devices such as door locks, water leak detectors, and motion sensors [24]. In fact, safety products or features are among the most popular SH products in all age groups [24,29]. The popularity appears to follow a chronological order, with the most recent innovations being the least preferred [24].…”
Section: Sh Service and Prevention Areasmentioning
confidence: 99%